Money supply: the impact on unemployment in Malaysia - Megat Tajuddin, Megat Zubairy (1994)
There is no doubt that money plays a vital role in an economy as the quantity of money and credit affects the level of output of goods and services. Presently, Malaysia is experiencing a rapid growth in its economy, relatively money supply will also increase which simultaneously increase its GDP and GNP. The increase in money supply has lead to the decrease in unemployment rate. However the central bank through monetary policy has control the circulation of money in the economy as the excess of money supply will lead to inflationary pressure in the country.